KONDISI FISIOLOGIS ITIK MOJOSARI BETINA YANG DIBERI RANSUM BERBEDA - Putra, Apri Satria; Sutrisna, Rudy; Santosa, Purnama Edy (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
This study aims to investigate the physiological responses mojosari duck females who were given rations with different nutrient content.Â  This study was conducted over three months from September to November 2015 held at the Laboratory of Animal Nutrition and Feed and enclosure Integrated Laboratory of the University of Lampung. Number of female ducks used as many as 64 birds and a cage 16 plots so that each plot contained 4 female ducks. Data were collected on the total number of ducks that exist in each treatment. Grouping ducks by weight. In the first group with body weight (125-150 g), group 2 (151-175 g), group 3 (176-200 g), group 4 (201-225 g). Ducks were divided into four treatment diets with different nutrient content, namely R1, R2, R3, and R4. The experimental design used is Design Group (RK). The data obtained were analyzed using analysis of variance. Based on the results of this study concluded that ration with different nutrient content was not significant (P> 0.05) on physiological responses mojosari duck female. Keywords: Female Mojosari Ducks, Rations, Nutrition, Physiological Responses